Kematangan Beragama Dalam Masa Pandemi Covid-19: Telaah Sosiologis atas Nasihat Imam Besar Istiqlal Nasaruddin Umar - Lestari, Puspita Ayu (The Sociology of Islam, 2021)
The pandemic Covid-19 outbreak has hit the economic, social, cultural, and mental health of some residents.. The effects of the outbreak not only make people have to pay more attention to their health. But it is also required to be able to reorganize social and improve mental and spiritual endurance. In these situation, religion forms a human dependence on the dimension of divinity, especially when the man experiences a terrible disaster and closes the door to rationality. Looking at the frenzy and diverse public responses, this paper tries to discuss religious maturity during the covid-19 pandemic by studying the advice of high priest Istiqlal Nasaruddin Umar. Through the theory of W.H. Clark, regarding the four criteria for religious maturity, this paper argues that one's religious maturity can be seen from its application in personal life and those around them during the Covid-19 pandemic.